2010
DOI: 10.3345/kjp.2010.53.11.965
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of spinal muscular atrophy type I

Abstract: PurposeThe life expectancy of patients with spinal muscular atrophy (SMA) type I is generally considered to be less than 2 years. Recently, with the introduction of proactive treatments, a longer survival and an improved survival rate have been reported. In this study, we analyzed the natural courses and survival statistics of SMA type I patients and compared the clinical characteristics of the patients based on their survival periods.MethodsWe reviewed the medical records of 14 pediatric patients diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Parents of a twelfth child declined nusinersen and the child died at 3 months of age. The median (range) number of nusinersen doses was 6 4–8. Nine children received mask ventilation and two children were ventilated via tracheostomy (TIV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents of a twelfth child declined nusinersen and the child died at 3 months of age. The median (range) number of nusinersen doses was 6 4–8. Nine children received mask ventilation and two children were ventilated via tracheostomy (TIV).…”
Section: Resultsmentioning
confidence: 99%
“…Until recently, SMA1 was the most common genetic disease resulting in death in infancy 4. Affected children usually present with symptoms before 6 months of age and historically died from respiratory failure by the age of 2 years 5…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic criteria for SMA reviewed in 1999 by the European Neuromuscular Center and motor skills were added as an important criterium; according to the new criteria, SMA type 1 patients are unable to sit unassisted, and the onset of the disease is in the prenatal period or within the first six postnatal months [15]. The life expectancy in SMA type 1 patients is less than 2 years [10]; however, recent studies have shown that the prognosis for SMA type 1 patients born after 1995 is better than for the ones born before 1995 [9]. In a cohort study of SMA type 1 patients, approximately 10% are reported to have lived beyond 5 years [3].…”
Section: Introductionmentioning
confidence: 99%
“…SMA is mainly characterized by the loss of alpha-motor neurons, leading to atrophy in the lower limbs and trunk muscles. However, restoration of SMN expression only in motor neurons is not sufficient to rescue SMN mice, nor does knocking out SMN in only motor neurons and oligodendrocytes phenocopy the whole-body loss of SMN[3,4]. Defects in heart, lung, pancreas[1,5,6,7], and liver have been identified in humans and in mouse models of SMA 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In a small study, birth weight was the only significant predictor of survival longer than 24 months in patients with SMA[4], suggesting that intrauterine growth may be related to prognosis. Similarly, in the mouse model of severe SMA (Smn -/- SMN2 tg/tg ), a subset of pups are born underweight, and these die at, or shortly after birth 11 .…”
Section: Introductionmentioning
confidence: 99%